BENTUK DAN PERUBAHAN FUNGSI MUSIK KONGKIL DI DESA BUNGKAL KABUPATEN PONOROGO - Rahayuningsih, Bina Kiki; Santoso, Iwan Budi (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2020)
Kongkil music was created in 1933 by Eyang Toinangun as a means of gathering the people of Bungkal Village as an effort to resist the Dutch invaders. Kongkil music is an ensemble consisting of instruments of kongkil, kedhang, saron, kethuk, kenong, kempul and gong. In the beginning, Kongkil's music brought songs created by its members with the theme of passion-building, because there was no legacy of the old repertoire of the predecessors. There was an innovation in the form of repertoire changes since 1975, namely bringing dolanan gendhing. Around 2000, Kongkil's music was in a vacuum, then it was revived in 2012 with a new repertoire that presented lancaran and langgam gendhing. The research entitled "The Form and Change of Kongkil Music Function in Bungkal Village, Ponorogo Regency" uses the concept of Edy Sedyawati's thought that changes in social structure and values will cause physical changes and the role of art itself in society. It also causes changes in the structure of forms. These changes cannot be avoided if the art is willing to live within the society. This study uses descriptive qualitative analysis methods.  From this study, it found several things related to the Kongkil Martapura music group, including: (1) History and regeneration of the Kongkil Martapura music group, (2) the forms of performances, instruments and repertoires presented, (3) the factors driving changes in function and its impact on intellectuals and contextual.